1997
DOI: 10.1021/jp971137n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Microporous Umbite, Penkvilksite, and Other Titanosilicates

Abstract: Synthetic analogues of the microporous minerals umbite (AM-2) and penkvilksite, polytype 2O (AM-3), have been prepared. The facile syntheses of two other titanosilicates, AM-1 and AM-4, have also been reported. AM-1 and the previously reported, layered titanosilicate known as JDF-L1 have been shown to have the same structure. AM-4 is a new microporous titanosilicate with a unique and unknown structure, containing eight different Na sites. All AM-n materials have been characterized by several techniques, viz. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
110
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 10 publications
9
110
0
1
Order By: Relevance
“…[13] Although its applications have not yet been widely studied, umbite, like the titanosilicates ETS-10 and ETS-4, possess framework structures built of MO 6 (M = Zr, Sn, Ti) octahedra and TO 4 (T = Si, Ge) tetrahedra. [14][15][16][17] These materials are good cation exchangers, and the ion-exchanged forms of Na + and Cs + -Zr-umbite, [18] NH 4 + , Li + , Na + , K + , Rb + and Cs + -Ti-umbite, [19] and Cs + and Sr 2+ -Sn-umbite [20] have been studied. Because of the onedimensional eight-membered ring channel (ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Although its applications have not yet been widely studied, umbite, like the titanosilicates ETS-10 and ETS-4, possess framework structures built of MO 6 (M = Zr, Sn, Ti) octahedra and TO 4 (T = Si, Ge) tetrahedra. [14][15][16][17] These materials are good cation exchangers, and the ion-exchanged forms of Na + and Cs + -Zr-umbite, [18] NH 4 + , Li + , Na + , K + , Rb + and Cs + -Ti-umbite, [19] and Cs + and Sr 2+ -Sn-umbite [20] have been studied. Because of the onedimensional eight-membered ring channel (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the onedimensional eight-membered ring channel (ca. 5.5 ϫ 2.7 Å), umbite-type materials do not adsorb N 2 , although they are suitable for adsorbing small molecules, such as water (a slow reversible rehydration of the material has been reported [15] ) and NH 3 , [21] and to retain by ion exchange mono and divalent cations. [18][19][20] Recently, stannosilicate and titanosilicate umbite tubular membranes have shown good performance in the separation of H 2 /N 2 mixtures achieving H 2 /N 2 separation factors higher than 40.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained solid (Zn-ETS-4), without affecting the healthy cells, can reduce the tumor cells down to 5%. These results are compared to another Zn-exchanged microporous titanosilicate (STS-Sofia titanium silicate, also known as AM-2-Aveiro-Manchester or synthetic umbite) 21,22 and natural clinoptilolite (CPT), which demonstrated that the specific host of incorporation of Zn 2+ is important for the efficiency and selectivity of the antitumor effect. All these materials have also been tested against HepG2 (human hepatocellular carcinoma cell line) cancer cells, indicating a lower efficiency but still superior cytotoxicity of Zn-ETS-4.…”
Section: Introductionmentioning
confidence: 99%
“…1). The microporous nature of penkvilksite has led to the synthesis of synthetic analogues to investigate their potential for ion-exchange (Lin et al 1997, Liu et al 1997. Merlino et al (1994) identified four possible maximum degrees of order (MDO) in polytypes of the penkvilksite structure, which can be produced from two kinds of layers:…”
Section: Introductionmentioning
confidence: 99%